2021
DOI: 10.21837/pm.v19i17.1006
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Issues of Tenancy Management Practice: The Case of Commercial Waqf Properties in Malaysia

Abstract: This paper concerns the sustainability of the commercial waqf properties (CWP) in regards to tenancy management (TM) since the waqf properties were underperformed due to large rental arrears in some states. The objective of the study is to investigate the issues of tenancy management that limit the achievement of the financial sustainability of CWP. This research adopts the qualitative approach which employing in-depth interviews at seven (7) CWP as a case study that covered the state of Johor, Selangor, Penan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Ja'afar and Usman ( 2009) Shamsuddin et al, (2004) asserted that traditional and cultural streets provide several activities such as hawkers and stalls, traditional trades, and religious places. Such activities create a vibrant and liveable environment, promote users' sense of place and identity, and reflect the character of a good city (Al-Obeidy 2015; Ali et al 2019Ali et al , 2020 (Sipan et al 2021). Sulaiman et al, (2017) found that many visible activities take place along the streets, giving users a welcoming and vibrant feeling to enjoy and stay longer in streets (Mehta & Bosson 2018;Ping-Li Chen 2014;Sulaiman et al 2017;Zhu et al 2013).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Ja'afar and Usman ( 2009) Shamsuddin et al, (2004) asserted that traditional and cultural streets provide several activities such as hawkers and stalls, traditional trades, and religious places. Such activities create a vibrant and liveable environment, promote users' sense of place and identity, and reflect the character of a good city (Al-Obeidy 2015; Ali et al 2019Ali et al , 2020 (Sipan et al 2021). Sulaiman et al, (2017) found that many visible activities take place along the streets, giving users a welcoming and vibrant feeling to enjoy and stay longer in streets (Mehta & Bosson 2018;Ping-Li Chen 2014;Sulaiman et al 2017;Zhu et al 2013).…”
Section: Research Backgroundmentioning
confidence: 99%